(untitled) (Eduscotech, 2023)
This study aims to answer two main questions: (1) how code mixing found in advertisement boards in Madiun City is implemented as a teaching media for reading comprehension, and (2) what difficulties are encountered by tenth-grade students of SMK Al Hikam Geger Madiun during the learning process. This research employed a descriptive qualitative design. The population consisted of tenth-grade students, and 27 students from class XB were selected using purposive sampling. Data were collected through observation and tests. A checklist was used to analyze the effectiveness of advertisement boards as teaching media, while tests measured students’ reading comprehension progress. The findings show that: (1) the use of advertisement boards containing code mixing is effective in teaching reading comprehension, and (2) students’ achievement increased significantly, with an average score reaching 80. The use of advertisement boards makes students more active and improves their comprehension in reading activities. Overall, code-mixing-based advertisement boards serve as an effective and engaging instructional media for vocational students.